Effect of oral clonidine premedication on attenuating haemodynamic response to laryngoscopy and intubation during general anaesthesia - Priyamargavi H.; Maruti Kambali; J. K., Jayakumar (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Laryngoscopy with or without tracheal intubation evokes a defense mechanism that in turn alters patients’ haemodynamic responses in terms of increased heart rate (HR) and arterial blood pressure (ABP). Aim of current investigation was to study the efficacy of orally administered clonidine in a dose of 3-3.5 µg/kg given 90 minutes prior to scheduled time of the surgery, in attenuating the adverse haemodynamic responses to laryngoscopy and intubation of the trachea. Methods: Eighty normotensive patients between 20-60 years of age and having ASA grade I/II physical status were subdivided in two groups with 40 patients in each; test group received clonidine in a dose of 3-3.5 mcg/kg of body weight orally, 90 min before surgery and control group did not receive clonidine premedication. Induction was done with Thiopentone intravenous injection (5 mg/kg), followed by succinylcholine (1-1.5 mg/kg). Results: Haemodynamic responses in terms of parameters like HR, systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP) were recorded at pre induction and at 1, 2, 3, 5 minutes following laryngoscopy. The 1-minute post induction values of SBP, DBP, MAP were significantly less in clonidine group (p<0.001) and the significance in listed parameters between two groups persisted until 5 minutes. Increase in HR was less in clonidine group than in control group. Conclusions: Premedication with oral clonidine 3-3.5 mcg/kg of body weight, 90 minutes before laryngoscopy and intubation is an efficient, simple and inexpensive method in attenuating the haemodynamic response generated due to laryngoscopy and intubation.